2023
DOI: 10.3390/met13010103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Fluid Disturbance Induced by Weld Reinforcement Height on the Corrosion of a Low Alloy Steel Weld

Abstract: Weld corrosion exists widely in the petrochemical industry and attracts great attention. Most research proves that weld corrosion originates from the material factors introduced during the welding process. However, it is noted that local fluid turbulence due to the weld reinforcement height (WRH) plays an important role in the non-uniform corrosion of welds in flowing media. Accordingly, the individual effect of the local flow on the weld corrosion of low alloy steel was analyzed by experiments and simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Various studies have been conducted in the past decades to understand the mechanism of the FAC of steel [20][21][22][23]. Initially, it was found that a higher flow velocity could enhance the mass transfer process at the interface, thereby accelerating the corrosion [24][25][26]. More recent studies have shown that, in addition to the flow velocity, different fluid regimes, such as bubbly flow, plug flow, stratified flow, wavy flow, and slug flow, play an important role in determining the FAC behavior [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted in the past decades to understand the mechanism of the FAC of steel [20][21][22][23]. Initially, it was found that a higher flow velocity could enhance the mass transfer process at the interface, thereby accelerating the corrosion [24][25][26]. More recent studies have shown that, in addition to the flow velocity, different fluid regimes, such as bubbly flow, plug flow, stratified flow, wavy flow, and slug flow, play an important role in determining the FAC behavior [27,28].…”
Section: Introductionmentioning
confidence: 99%